Sensing surface PEGylation with microcantilevers - Backmann, Natalija (Beilstein-Institut, 2010)
Polymers are often used to modify surface properties to control interfacial processes. Their sensitivity to solvent conditions and ability to undergo conformational transitions makes polymers attractive in tailoring surface properties with specific functionalities leading to applications in diverse areas ranging from tribology to colloidal stability and medicine. A key example is polyethylene glycol (PEG), which is widely used as a protein-resistant coating given its low toxicity and biocompatibility. We report here a microcantilever-based sensor for the in situ characterization of PEG monolayer formation on Au using the “grafting to” approach. Moreover, we demonstrate how microcantilevers can be used to monitor conformational changes in the grafted PEG layer in different solvent conditions. This is supported by atomic force microscope (AFM) images and force–distance curve measurements of the microcantilever chip surface, which show that the grafted PEG undergoes a reversible collapse when switching between good and poor solvent conditions, respectively.